Impact of smoking status and concomitant medications on the effect of high-dose N-acetylcysteine on chronic obstructive pulmonary disease exacerbations: A post-hoc analysis of the PANTHEON study. (February 2019) - Papi, Alberto; Zheng, Jinping; Criner, Gerard J.; Fabbri, Leonardo M.; Calverley, Peter M.A.
Abstract: Background: N-acetylcysteine (NAC) 600 mg twice daily is a well-tolerated oral antioxidant mucolytic that reduces the risk of moderate to severe chronic obstructive pulmonary disease (COPD) exacerbations. PANTHEON was one of the largest studies to evaluate NAC in COPD. It recruited current, ex- and never-smokers, concomitantly treated with other medications, and used a symptom-based definition of COPD exacerbations rather than the conventional healthcare resource utilisation (HCU) criteria. Methods: This manuscript reports post-hoc analyses of the PANTHEON dataset investigating whether smoking status or use of concomitant medications influenced the efficacy of NAC in terms of reducing exacerbations, defined according to HCU. Results: Compared with placebo (N = 482), NAC (N = 482) reduced the rate of HCU events by 20% (p = 0.0027), with a larger effect in current/ex-smokers (23%; p < 0.01). In patients receiving NAC and long-acting inhaled bronchodilator(s) but no ICS, there was a 60% reduction in the rate of exacerbations compared to those receiving placebo, long-acting bronchodilator(s) and ICS (p < 0.0001). Conclusions: Overall, these post-hoc hypothesis-generating analyses confirm that NAC reduces the rate of COPD exacerbations, particularly in patients with COPD who have a significant smoking history, and in those not treated with ICS. NAC may provide an alternative to ICS-containing combinations in these patient subgroups. Clinical trial registration: Chinese Clinical Trials Registry, ChiCTR-TRC-09000460. Highlights: N-acetylcysteine (NAC) 600 mg twice daily is an oral antioxidant mucolytic. PANTHEON was one of the largest studies to evaluate NAC in COPD. These post-hoc analyses of PANTHEON confirm that NAC reduces exacerbations. The effect on exacerbations was larger in current/ex-smokers. NAC reduced exacerbations by 60% vs ICS when added to long-acting bronchodilators.